Person-centred care for dementia patients (back-end and front-end development) - Ng, Magdeline Xuan Lynn (Nanyang Technological University, 2024)
Dementia is a neurological disorder that progressively weakens cognitive abilities, induces memory loss, and alters personality. Singapore's ageing population, driven by increasing life expectancy and low fertility rates, faces a significant challenge. With citizens aged 65 and above constituting almost one-fifth of the population—a rise of 11.7% over a decade—dementia cases are on the rise. Presently, 1 in 10 adults over 60 in Singapore suffers from dementia, a number expected to reach 152,000 by 2030, tripling from 45,000 in 2015. This underscores the pressing need for healthcare services in Singapore's ageing society. Despite the absence of pharmacologic cures or effective long-term treatments, non-pharmacological interventions, particularly person-centred care, address behavioural and psychological symptoms. The Person-Centred Care For Dementia Patients (PEAR) system was developed to provide individualised care tailored to each patient's unique needs, preferences, and objectives. Aligned with Singapore's National Electronic Health Record (NEHR) system, PEAR facilitates comprehensive patient care coordination and informed decision-making. In contributing to the PEAR system, the author focused on enhancing its functionality and usability. This involved implementing API endpoints such as "Manage activities", "Activity Preference" and "Routine", ensuring seamless data management. Features such as disabling modifications for inactive patient records and enhancing data representation in patient’s table columns were introduced. Additionally, thorough input validation was implemented through JQuery and .NET Razor views. Referring to requirements from the Product Owner's feedback, the author ensured stringent validation both on the browser and backend server, leading to a more robust and user-friendly application.